Study on Environmental Risk Assessment and Management Methods for the Recycle of Industrial Solid Waste. (March 2019) - Yang, Shuo; Guo, Huiting; Wang, Xiuteng
Abstract: Industrial solid waste demonstrates both the resources and pollution attributes when be used as raw materials for production. Hence, it is critical to prevent the industrial solid waste from endangering the human beings and environment when it is recycled, so to balance the resource efficiency and safety. The present study reviewed the development of relevant theories and methods in the relation with environmental risk assessment and management worldwidely. The characteristics of industrial solid waste are also taken into consideration. The pollutants in the industrial solid waste are classified as the human-health hazard type and product-quality damaging type depending on whether the pollutant can pose negative effect on human health, and only the human-health hazard type is regarded as the subject for risk assessment and management. Based on the classification and simplification, this study proposed the environmental risk assessment and management methods for the recycle process of the industrial solid. The aluminum extraction from coal fly ash was analyzed and the risk was assessed by applying the "Four-step Method". The corresponding risk surveillance scheme was developed based on the risk assessment. Both the method developed by the study as well as the case analysis may provide some insight for relevant research.